The Myths of Creativity: The Truth About How Innovative Companies and People Generate Great Ideas - David Burkus (Jossey- Bass, 2014)
How to get past the most common myths about creativity to design truly innovative strategies We tend to think of creativity in terms reminiscent of the ancient muses: divinely-inspired, unpredictable, and bestowed upon a lucky few. But when our jobs challenge us to be creative on demand, we must develop novel, useful ideas that will keep our organizations competitive. The Myths of Creativity demystifies the processes that drive innovation. Based on the latest research into how creative individuals and firms succeed, David Burkus highlights the mistaken ideas that hold us back and shows us how anyone can embrace a practical approach, grounded in reality, to finding the best new ideas, projects, processes, and programs.